Profitability vs sustainability: Prelimary finding on green innovation adoption in information technology usage - Jamaludin, Norzalila; Ahmad, Hartini; Ramayah, T. (2012)
The area of Green information technology (IT) has become a significant issue for current organizations around the world because it is not only affects their profit margins but also the sustainability of environment through the increased in energy costs.Specifically, in focusing of carbon emissions that meant organizations are motivated more than ever to monitor their sustainability environment. The imperative roles of carbon emissions into the area of Green IT where they believed in reductions of energy emissions can be made. Reviews of the literature(i.e., DOI theory, TOE theory and technology adoption) and preliminary findings in manufacturing and services firms are presented. We classify firms into three main groups based on the earliness of green innovation adoption, namely adopters, prospectors, and laggards.Three groups of factors influencing adoption decisions are identified, including organizational, technology and environmental factors.This paper accentuates the importance of adoption of Green IT, which can have a detrimental effect on business profitability and sustainability.Therefore, the results are interpreted and subsequently discussed.The paper is relevant to both researchers and business practitioners.